Preconceito racial e de classe social em crianças: O papel mediador dos valores humanos - Ramalho, Jaqueline Vilar Greco (2016)
This thesis aimed to investigate the expressions of racial prejudice and social class from comparative studies of children attending public and private schools. The specific objectives were: to investigate the racial self-identification of these children and analyze the mediating role of adherence to values systems in the expressions of these prejudices. To achieve these goals, there were three empirical studies. The first investigated the brand recognition of children's clothing and the relationship made by the participants between brands and social class (rich and poor). The second sought to develop a measurement strategy of racial prejudice through the relationship made by the participants of the marks of children's clothing and skin color of the dolls (black and white). The third investigated the preferences of the participants in relation to white and black dolls, dressed in branded clothes and unbranded. This study also investigated the mediating role of Schwartz's value systems in the preference of the participants. In study1, (N = 30) the results showed that although children in general have not recognized the marks when asked about rich and poor brands, managed to differentiate in both schools, 46.66% of children said that poor children do not use the marks given for not having money, signaling perception of the economic and social status by children. In Study 2 (N = 80) together, the results showed no differences between the use of the marks and the color of dolls presented, although the white doll (M = 2.55, SD = 0.77) has been ranked as the richest the black (M = 1.75, SD = 0.92), t (76) = 5.43, p <0.001. As for the self-identification of children in the public school the children if autoidentification as black, although at the time of identification with the color of the dolls have been identified with the white doll, this phenomenon suggests the hypothesis of whiting. In Study 3 (N=232), the results showed a congruence between racial belonging as the proximity to the dolls even this being black and dressed in clothing unbranded. In private school, the children demonstrated proximity to the black doll, signaling the possibility of internalization of antidiscrimination norm. Regarding the mediation of human values, the chances of this thesis were confirmed, since both the public school and the private school, selfpromotion values predicted preference for the white doll positively and negatively by the black doll.